Identifikasi risiko malnutrisi dan evaluasi status nutrisi pasien kanker anak dengan pengobatan kemoterapi - Agus Santosa; Sri Mulatsih; Susetyowati Susetyowati (Jurnal Gizi Klinik Indonesia, 2019)
Identification of malnutritional risk and nutrition status evaluation of pediatric cancer patients with chemotherapy treatmentBackground: Hospitalized childhood cancer patients had a high risk for malnutrition, either caused by the disease or effects of cancer treatment. Malnutrition in cancer patients gives negative impacts on treatment outcomes in the form of increasing morbidity and mortality rates. Nutrition screening for identifying malnutrition risks could prevent malnutrition in hospitals.Objectives: Investigating the influence of malnutrition risk during hospitalization on the changes in the nutritional status of childhood cancer patients with chemotherapy treatment. Methods: This research was observational research with the nested case-control design. The research subjects were childhood cancer patients aged 2-18 years old meeting the inclusion criteria. They were 64 in number consisting of the case group involving 32 patients and a control group involving the rest. During hospitalization, analyses of nutritional intake, change in body weight, nutritional status, and hospitalization period. Furthermore, the analyses of the influence of malnutrition risk on the outcome between those two groups were then compared. Results: There was a significant influence of malnutrition risk on less energy intake (p<0.001), less protein intake (p=0.002), weight loss >2% (p<0.001), poor nutritional status based on the BMI/U (p=0.011), and longer hospitalization (p=0.034). The group of patients with malnutrition risks had risks of 15.5 (CI 95%: 3.991-63.359) times higher for less energy intake, 6.12 (CI 95%: 1.675-24.906) times higher for less protein intake, and 45.3 (CI 95%: 5.666-1940.768) times higher for weight loss > 2% than the group of patients without malnutrition risks.Conclusions: Patients with a significant risk of malnutrition had less energy and protein intake, weight loss > 2%, poor nutritional status based on BMI/U, and longer hospitalization.